2002
DOI: 10.1136/bmj.325.7376.1323
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of appropriately trained nurses in preoperative assessment: randomised controlled equivalence/non-inferiority trial

Abstract: Objective To determine whether preoperative assessments carried out by appropriately trained nurses are inferior in quality to those carried out by preregistration house officers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 3 publications
3
40
0
Order By: Relevance
“…These systems are now regarded as the standard model of surgical care in Australia [7,8] and North America [9,11,36], and increasingly in Europe [10,49]. We found no comprehensive, formal cost-effectiveness evaluations of the Perioperative System.…”
Section: Discussionmentioning
confidence: 96%
“…These systems are now regarded as the standard model of surgical care in Australia [7,8] and North America [9,11,36], and increasingly in Europe [10,49]. We found no comprehensive, formal cost-effectiveness evaluations of the Perioperative System.…”
Section: Discussionmentioning
confidence: 96%
“…We examined the baseline tables of the trials and did not find any clear evidence of differences between groups, although subversion would have to have been quite substantial for this to be observable 5. Interestingly, one trial reported using a block size of four (and opaque envelopes) and stratified the randomisation by site 18. This resulted in numerical imbalances of 11 at two of the three sites, which should not have occurred using a block size of 4.…”
Section: Current Practicementioning
confidence: 99%
“…The newness of the consultant role means that few rigorous research evaluations have yet been carried out, although studies have explored other new nursing roles (Cameron & Masterson 2000, Collins et al 2000, Nicholson et al 2005. Comparisons between the clinical nurse specialist or nurse practitioner and the doctor's role have reported no difference or statistically significantly better outcomes from nurses (Shum et al 2000, Horrocks et al 2002, Kinley et al 2002, Moore et al 2002, Sharples et al 2002, Griffiths et al 2004. Such comparison would be appropriate for consultant nurses/ midwives only if theirs is a medical substitution role.…”
Section: Evaluation Of the Consultant Rolementioning
confidence: 99%